The influence of boron on the kinetics of phase formation, the dislocation structure, and the diffusion parameters of nickel - Azarenkov, N.А.; Lytovchenko, S.V.; Semenenko, V.Е.; Styervoyedov, N.G. (Вопросы атомной науки и техники, 2018)
The comparative characteristic of the processes of the kinetic formation of nickel borides, the dislocation structure and the state of interphase boundaries in nickel alloys obtained by the electrochemical method and unidirectional crystallization is carried out. The effect of boron on the diffusion parameters of micro- and macro-alloyed nickel alloys is definitely determined.